Penerapan e-Procurement Dalam Proses Pengadaan Barang Dan Jasa Pemerintah Guna Mendukung Ketahanan Tata Pemerintahan Daerah (Studi pada Unit Layanan Pengadaan Barang dan Jasa Pemerintah Kabupaten Penajam Paser Utara Provinsi Kalimantan Timur) - Rahmat Hidayat (Universitas Gadjah Mada, 2015)
ABSTRACTThe purpose of this study was to analyzed the application of the principle of e-Procurement in ProcurementServices Unit in the Government District Penajam Paser Utara, examines the obstacles faced by the ProcurementServices Unit in the process procurement of goods and services by the government through e-procurement process andto formulated strategies that were done overcome by Procurement Services Unit to the obstacles in implementation of e-procurement to supported the resilience of governance in the district Penajam Paser Utara.The research method used was descriptive method with quantitative and qualitative approaches. The data wascollected through questionnaires, interviews, observation and documentation. The measurement applied Likert scale was applied to 32 Procurement Services Unit offi cers and informant interviews to 3 people who knew in depth about the implementation of e-procurement in Penajam Paser Utara. The research showed the application of the principles of e-procurement in district Penajam Paser Utara districtthat generally was going according to applicable regulations, but there were still some obstacles in its application, namely Procurement Services Unit institution, infrastructures,and human resources . It require the government efforts to resolvethese obstacles in order to supported the resilience of regional governance in Penajam Paser Utara district.ABSTRAKTujuan penelitian ini untuk menganalisis penerapan prinsip e-procurement pada Unit Layanan Pengadaan Barang dan Jasa di Pemerintah Kabupaten Penajam Paser Utara, mengkaji kendala yang dihadapi Unit Layanan Pengadaan dalam proses pengadaan barang dan jasa pemerintah melalui proses e-procurement serta untuk merumuskan strategi yang dilakukan Unit Layanan Pengadaan dalam mengatasi kendala penerapan e-procurement guna mendukung ketahanan tata pemerintahan daerah di Kabupaten Penajam Paser Utara. Metode penelitian yang digunakan yaitu metode penelitian deskriptif dengan perpaduan kuantitatif dan kualitatif. Teknik pengumpulan data dilakukan dengan penyebaran kuesioner, wawancara,observasi dan studi pustaka. Pengukuran menggunakan skala Likert kepada 32 orang petugas ULP dan wawancara kepada 3 orang informan yang mengetahui secara mendalam tentang penerapan e-procurement di Kabupaten Penajam Paser Utara. Hasil penelitian menunjukkan penerapan prinsip e-procurement di Kabupaten Penajam Paser Utara secara umum sudah berjalan sesuai peraturan yang berlaku namun masih terdapat beberapa kendala dalam penerapannya, yakni kelembagaan ULP, Infrastruktur, dan SDM. Untuk itu diperlukan strategi pemerintah daerah dalam mengatasi kendala tersebut guna mendukung ketahanan tata pemerintahan daerah di Kabupaten Penajam Paser Utara.